2020
DOI: 10.1038/s41467-020-16490-4
|View full text |Cite
|
Sign up to set email alerts
|

A powder-metallurgy-based strategy toward three-dimensional graphene-like network for reinforcing copper matrix composites

Abstract: Three-dimensional graphene network is a promising structure for improving both the mechanical properties and functional capabilities of reinforced polymer and ceramic matrix composites. However, direct application in a metal matrix remains difficult due to the reason that wetting is usually unfavorable in the carbon/metal system. Here we report a powdermetallurgy based strategy to construct a three-dimensional continuous graphene network architecture in a copper matrix through thermal-stress-induced welding be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
77
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 192 publications
(79 citation statements)
references
References 50 publications
2
77
0
Order By: Relevance
“…In such structures, graphene flakes (GFs) can be considered as an intact network which leads to the increase in shear stress. [16][17][18] It was already shown that graphene networks like CG can increase the strength of the metal matrix and simultaneously, composite remains good tensile ductility. [19,20] Previously, composites were successfully obtained based on CG and molybdenum oxide, [21] CG and carbon nanotubes (CNT), [22] CG and Ni, [15] graphene network and Cu, [16][17][18] etc.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In such structures, graphene flakes (GFs) can be considered as an intact network which leads to the increase in shear stress. [16][17][18] It was already shown that graphene networks like CG can increase the strength of the metal matrix and simultaneously, composite remains good tensile ductility. [19,20] Previously, composites were successfully obtained based on CG and molybdenum oxide, [21] CG and carbon nanotubes (CNT), [22] CG and Ni, [15] graphene network and Cu, [16][17][18] etc.…”
Section: Introductionmentioning
confidence: 98%
“…[16][17][18] It was already shown that graphene networks like CG can increase the strength of the metal matrix and simultaneously, composite remains good tensile ductility. [19,20] Previously, composites were successfully obtained based on CG and molybdenum oxide, [21] CG and carbon nanotubes (CNT), [22] CG and Ni, [15] graphene network and Cu, [16][17][18] etc. Most of the previous studies on metal/graphene composites were aimed to understand the technological issues, such as fabrication of the composites or improving adhesion between graphene and metal.…”
Section: Introductionmentioning
confidence: 98%
“…We achieved this integration without the use of thermal annealing or high pressure as recently reported for 3D graphene‐Cu networks. [ 68 ] Besides the energy‐efficiency benefits, the spatial patterning capabilities are an additional plus that makes our method attractive for electronics implementation and other applications, including temperature sensors (Figure S24, Supporting Information). Beyond the photothermal and mechanical benefits from Al NPs, we further exploit their photonic properties in the photocatalytic oxidation of TMB.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, if the wettability between nanophases and molten metals/alloys is bad, nanophases are easily sintered or agglomerated, due to the hightemperature Brownian motion. In these cases (e.g., Cu with grapheme [60], Al with Al 2 O 3 [61], etc. ), the ball milling method using powder metallurgy would be important to obtain high-quality MMNCs [14,33], as shown in Fig.…”
Section: Bulk Processing Techniquesmentioning
confidence: 99%